Moderating Effect of Growth Need Strength on the Relationship between Job Characteristics and Job Satisfaction - Mohd Nizam Sarkawi; Abdul Rahman Jaafar; Jauriyah Shamsuddin; Noor Fareen Abdul Rahim (International Review of Management and Marketing, 2016)
This study is to determine the moderating effect of Growth Need Strength [GNS] between self-esteem and job satisfaction among SRN’s. Data were collected through survey using questionnaire. This study employed stratified random sampling involving a total of 390 nurses at selected general hospitals. The finding of the study contributes in the specific area of literature, theory and also in research design. The results of this study suggest that the GNS as moderator have played significant important role between job characteristics and job satisfaction. It is also provide a much better conducive working environment and by incorporating policies that can improve job satisfaction.